Predictive Analysis to Support Fog Application Deployment - Brogi, Antonio; Forti, Stefano; Ibrahim, Ahmad (Fog and Edge Computing, 2019)
The iFogSim is a simulation tool for fog computing scenarios. This chapter presents an extended version of FogTorchΠ, a prototype based on a model of the Internet‐of‐Things (IoT)+Fog+Cloud scenario to support application deployment in the Fog. It introduces a motivating example of a smart building application and describes FogTorchΠ predictive models and algorithms. The chapter presents and discusses the results obtained by applying FogTorchΠ to the motivating example. It provides some related work and a comparison with the iFogSim simulator. The chapter shows how both iFogSim and FogTorchΠ can be used together to solve the same input scenario. It reviews the virtual reality game case study employed for iFogSim, executed FogTorchΠ over it and compares the results obtained by both prototypes. The chapter also highlights future research directions and draws some concluding remarks.